Research 2.0 and the future of information literacy - Koltay, Tibor; Spiranec, Sonja; Karvalics, Laszlo Z., 1961- (Amsterdam : Chandos Publishing is an imprint of Elsevier, 2016)
Annotation This volume summarises the most important and up-to date theory of abstracting, in addition to giving advice and examples on writing different kinds of abstracts. It discusses the length, functions and basic structure of abstracts, outlining a new approach to informative and indicative abstracts. It is designed to assist specialist researchers who work, and publish, in different fields, but also write author abstracts and is an ideal resource for those interested in library and information science and information literacy.
The Relationship of Information Literacy to Information Overload and Personal Information ManagementChapter 3: Transformations of Information Literacy: From Bookshelves to the Web 2.0; The Practical Level: From Bibliographic Instruction to IL; Theoretical Perspectives Influencing Shifts in IL; The Information Environment as a Principal Driver of IL Transformations; Chapter 4: Conclusion: Shaping Forces, Future Challenges; References; Index; Back Cover.
Includes bibliographical references and index.
English.
Keywords: Information literacy; Research -- Methodology; Media literacy